Disparitas Putusan Hakim dalam Tindak Pidana Narkotika - A.A Ngr Rai Anjasmara Putra; I Made Sepud; I Nyoman Sujana (Fakultas Hukum Universitas Warmadewa, 2020)
Disparity in Indonesia has a meaning of distinction, in the Science of law disparity is the difference of ruling that is dropped by judges in the same criminal act, judges in dropping the ruling often occur disparity A verdict in the same case. One of them in the case of narcotics criminal act where there are perpetrators who are in prison and there are perpetrators who are in a rehabilitation ruling in this case a judge must have an understanding and view that a narcotics abuse is a victim that must be healed of a dependency disease. In the proceedings, the judges have the authority to examine and disconnect the judges in the case of a consideration which can be incriminating or alleviating the suspect in order to create justice. The purpose of this research is to know how the authority of a judge in the break of criminal acts and basic consideration of judges so that there is a disparity of verdict in narcotics criminal act. The method used is the type of normative research by conducting a statutory approach, conceptual approach and a case approach analyzed using a systematic technique with a descriptive analytical presented Assisted by the source of the collected legal materials and interpreted. Judge in a narcotics criminal offence authorized to examine the evidence tool, witness information, information defendants, and information experts and in the criminal offence break the judges are authorized to determine the defendant in the rehabilitation or sentenced to prison Proceed to basic consideration of judges in disconnecting disparity against narcotic criminal acts due to different deeds committed by the defendant where if the defendant is only a user then the decision received will be lighter and if The defendant as a distributor will give punishment